ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN RETRIBUSI IZIN MENDIRIKAN BANGUNAN DI KABUPATEN KAMPAR - Sofiandi Sofiandi; Syapsan Syapsan; Dahlan Tampubolon (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
This study aims to analyze what influences the receipt of building permit fees in Kampar Regency. This study uses secondary data obtained from the Central Statistics Agency (BPS) and the DPTSP of Kampar Regency in 2010 - 2019, while the data analysis technique is to use multiple linear regression methods. The results of the study found that the number of buildings had a significant positive effect on IMB fees in Kampar Regency. Meanwhile, PDRB has no positive effect on receiving IMB fees in Kampar Regency. The implementation of policies carried out in Kampar District to increase the receipt of IMB fees is to increase public awareness in managing IMB permits.